Dye–collagen interactions. Mechanism, kinetic and thermodynamic analysis1. Issue 71 (2nd August 2015) - Tuttolomondo, Maria Victoria; Galdopórpora, Juan Manuel; Trichet, Lea; Voisin, Hugo; Coradin, Thibaud; Desimone, Martin Federico
<x xml:space="preserve">Abstract</x> Dye–collagen interactions. Mechanism, kinetic and thermodynamic analysis.